A novel pathogenic variant in OFD1 results in X‐linked Joubert syndrome with orofaciodigital features and pituitary aplasia. Issue 6 (20th March 2019) - Aljeaid, Deema; Lombardo, Rachel C.; Witte, David P.; Hopkin, Robert J.
Abstract : Orofaciodigital syndrome type I and X‐linked recessive Joubert syndrome are known ciliopathic disorders that are caused by pathogenic variants in OFD1 gene. Endocrine system involvement with these conditions is not well described. We present the first report of a newborn male with a novel hemizygous variant in OFD1 gene c.515T>C, (p.Leu172Pro) resulting in X‐linked Joubert syndrome and orofaciodigital features with complete pituitary gland aplasia and subsequent severe hypoplasia of peripheral endocrine glands. This clinical report expands the phenotypic spectrum of endocrine system involvement in OFD1 ‐related disorders and suggests that OFD1 gene may be related to pituitary gland development.